Dopers in uniform: the hidden world of police on steroids - Hoberman, John M. (Terry and Jan Todd series on physical culture and sports, 2017)
What we know about cops on steroids -- Police chiefs and the steroid dilemma -- Police unions and steroids -- The gym culture : where muscular cops meet -- Steroids in the military